2022
DOI: 10.1002/cptc.202200127
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐Bright Near‐Infrared Sulfonate‐Indolizine Cyanine‐ and Squaraine‐Albumin Chaperones: Record Quantum Yields and Applications

Abstract: The design of bright, high quantum yield (QY) materials in the near‐infrared (NIR) spectral region in water remains a significant challenge. A series of cyanine and squaraine dyes varying water solubilizing groups and heterocycles are studied to probe the interactions of these groups with albumin in water. Unprecedented, ′ultra‐bright′ emission in water is observed for a sulfonate indolizine squaraine dye (61.1 % QY) and a sulfonate indolizine cyanine dye (46.7 % QY) at NIR wavelengths of >700 nm and >800 nm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 64 publications
(117 reference statements)
0
12
0
Order By: Relevance
“…3,4 Our group has previously reported an indolizine squaraine dye (SO3SQ, Scheme 1) that demonstrates "ultra-bright" switchon near infrared (NIR, 700-1000 nm) emission upon binding to albumin in fetal bovine serum (FBS), human serum albumin (HSA), and on latent blood stains. [11][12][13] Albumin has previously been shown to enhance dye emission for sensors and for in vivo biological imaging; however, these reports have not been found to be applicable in forensic imaging (Table S2 †). 9, [14][15][16][17][18][19][20][21][22][23][24][25] The albumin-SO3SQ complex displays longer lived emission (on the order of days to weeks), more selectivity for blood (since albumin is specic to and ubiquitous in blood), 26,27 and leaves DNA less perturbed than with oxidizing solutions or ultraviolet (UV, 100-400 nm) light.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Our group has previously reported an indolizine squaraine dye (SO3SQ, Scheme 1) that demonstrates "ultra-bright" switchon near infrared (NIR, 700-1000 nm) emission upon binding to albumin in fetal bovine serum (FBS), human serum albumin (HSA), and on latent blood stains. [11][12][13] Albumin has previously been shown to enhance dye emission for sensors and for in vivo biological imaging; however, these reports have not been found to be applicable in forensic imaging (Table S2 †). 9, [14][15][16][17][18][19][20][21][22][23][24][25] The albumin-SO3SQ complex displays longer lived emission (on the order of days to weeks), more selectivity for blood (since albumin is specic to and ubiquitous in blood), 26,27 and leaves DNA less perturbed than with oxidizing solutions or ultraviolet (UV, 100-400 nm) light.…”
Section: Introductionmentioning
confidence: 99%
“…Albumin is the most abundant protein in the blood serum and, therefore, makes an ideal target for sensing blood. , NIR-emitting dyes are garnering a lot of attention due to their uniquely high emission output, which can be exploited for biosensing and bioimaging. , Small molecule organic fluorophores that emit in the NIR are advantageous in that they result in increased resolution of internal biological systems due to decreased scattering and absorption of NIR light; some undergo a sharp increase in fluorescence quantum yield (Φ F ) upon an interaction with specific biomolecules and demonstrate biocompatibility with important blood proteins and nucleic acids. Recently, a NIR emissive sulfonate indolizine-donor-based squaraine dye (SO 3 SQ) was observed to exhibit a remarkably intense fluorescence quantum yield (Φ F of 58%) in the presence of fetal bovine serum. , A further increase in Φ F to 61.1% was observed when SO 3 SQ was dissolved in human serum albumin (HSA). , An investigation of this phenomenon revealed that the source of the enhancement was the interaction between the dye and the heme cleft site of albumin, where the dye was locked into an “ultrabright” configuration . However, we report herein that SO 3 SQ is noticeably less fluorescent in whole blood compared to that in a solution containing pure albumin protein, likely due to the highly complex microenvironment in the blood matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Albumin is the most abundant protein in the blood serum and, therefore, makes an ideal target for sensing blood. 1,2 NIRemitting dyes are garnering a lot of attention due to their uniquely high emission output, which can be exploited for biosensing and bioimaging. 3,4 Small molecule organic fluorophores that emit in the NIR are advantageous in that they result in increased resolution of internal biological systems due to decreased scattering and absorption of NIR light; some undergo a sharp increase in fluorescence quantum yield (Φ F ) upon an interaction with specific biomolecules and demonstrate biocompatibility with important blood proteins and nucleic acids.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations